Eliciting Permanent and Transitory Undeclared Work from Matched Administrative and Survey Data - Peter Elek; János Köllő (Institute of Labor Economics (IZA), 2017)
We study the undeclared work patterns of Hungarian employees in relatively stable jobs, using a panel dataset that matches individual-level self-reported Labour Force Survey data with administrative records of the Pension Directorate for 2001–2006. We estimate the determinants of undeclared work using Heckman-type random-effects panel probit models, and develop a two-regime model to separate permanent and transitory undeclared work, where the latter follows a Markov chain. We find that about 6-7 per cent of workers went permanently unreported for six consecutive years, and a further 4 per cent were transitorily unreported in any given year. The models show lower reporting rates – especially in the permanent segment – among males, high-school graduates, those in agriculture and transport, various forms of atypical employment, and small firms. Transitory non-reporting may be partly explained by administrative records missing for technical reasons. The results suggest that (i) the 'aggregate labour input method' widely used in Europe can indeed be a simple yet reliable tool to estimate the size of informal employment, although it slightly overestimates the true magnitude of black work (ii) the long-term pension consequences of undeclared work are substantial because of the high share of permanent non-reporting.
Keywords: C23; C25; H26; J46; 330; random-effects panel probit with endogenous selection; matched administrative-survey data; labour input method; undeclared work; Markov chain